2022
DOI: 10.2319/082321-659.1
|View full text |Cite
|
Sign up to set email alerts
|

Dental arch changes after anterior open bite treatment in the mixed dentition produced by miniscrew-supported palatal crib vs conventional fixed palatal crib:

Abstract: Objectives To evaluate the dental arch changes produced by the miniscrew-supported palatal crib (MSPC) and the conventional fixed palatal crib (CFPC) after the treatment of patients with anterior open bite (AOB) attributed to the tongue-thrusting habit in the mixed dentition stage. Materials and Methods A total of 26 children aged 8 to 11 years with an AOB were randomly distributed into two equal groups; the MSPC group was tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…A previous study by de Brito Vasconcelos et al 15 Fouda et al 18 , who documented a significant increase in the length of incisors' clinical crown by 0.33±0.64 mm and 0.49±0.63 mm, respectively. This increase can be explained by the fact that, during extrusion of the incisors, the gingiva may not conform to the tooth, which may increase the clinical crown height.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…A previous study by de Brito Vasconcelos et al 15 Fouda et al 18 , who documented a significant increase in the length of incisors' clinical crown by 0.33±0.64 mm and 0.49±0.63 mm, respectively. This increase can be explained by the fact that, during extrusion of the incisors, the gingiva may not conform to the tooth, which may increase the clinical crown height.…”
Section: Resultsmentioning
confidence: 82%
“…This finding was consistent with those of de Brito Vasconcelos et al 15 Regarding the effect of the extrusion arch on the upper permanent molars, there was no statistically significant difference in their anteroposterior position (p>0.005). A randomized clinical trial conducted by Fouda et al 18 showed that there was a significant mesial tipping of the upper first molar by 1.42 ±0.99 mm and 0.53±0.32 mm in the conventional fixed palatal crib group and the miniscrew-supported palatal crib group respectively.…”
Section: Resultsmentioning
confidence: 99%
“…2023, 13, 7474 2 of 11 Skeletal anchorage in the anterior palate is optimal for supporting various treatment mechanics, including distalization [8], rapid maxillary expansion [9], space closure [10], intrusion mechanics [11], canine disimpaction [12][13][14] and final incisor position relative to the facial profile esthetics [15,16]. Furthermore, orthodontists can address more complex clinical situations, such as severe open bite [17], impacted teeth [18] or mixed dentition [19].…”
Section: Introductionmentioning
confidence: 99%